PENGARUH PENAMBAHAN SUSU SKIM TERHADAP HASIL DNA METAGENOMIK DIISOLASI DARI TANAH HUTAN MANGROVE - Frida Oktaningtias Widiarthi, Ni Putu; Ratnayani, Ketut; Wirajana, I Nengah (Jurnal Kimia (Journal of Chemistry), 2014)
Cell lysis is the most important step for quality and quantity of metagenomic DNA isolated from an environmental samples. The aim of the research was to compare the quality (integrity and purity) of the metagenomic DNA isolated using the direct cell lysis method from mangrove forest soil with and without skim milk. The total of metagenomic DNA isolated from mangrove forest soil result was analyzed by the spectrophotometric UV-Vis method at ? 230, 260, and 280 nm; and also by using the agarose gel electrophoresis. The results showed that metagenomic DNA can be isolated from mangrove forest soil. The agarose gel electrophoresis results showed that the total DNA quality obtained by the direct cell lysis using buffer lysis with skim milk was relatively less fragmented and the band intensity of DNA was higher compared with direct cell lysis using buffer lysis without skim milk. The results of spectrophotometry indicated that the purity of DNA isolated with and without skim milk was not significantly different against the humic acid (ratio on A 260/230 ). As shown by the A 260/280 ratio, the total DNA isolated without skim milk had higher purity level than with skim milk.
Keywords: skim milk, metagenomics DNA, lysis, mangrove forest soil